Integrasi Linguistik dan Kajian Keagamaan: Peran Kajian Bahasa dalam Kajian KeIslaman - Saifuddin Ahmad Husin (STAI AL FALAH Banjarbaru, 2022)
AbstractKnowledge integration has been studied as the process of incorporating new information into a body of existing knowledge with an interdisciplinary approach. Language is not only the object of scientific study of linguistics, but also the object of study of other related disciplines. The importance of language in many studies and disciplines of knowledge has led to its status as a condition sin qua non to true understanding of other scientific objects of disciplines of knowledge. The mastery of Arabic language for example is a must for the study of Islamic religious texts. The religion of Islam places language on a very high position that it is explicitly mentioned in the Qur’an as one of the signs of the existence of God. Keywords: Islam, Linguistics, Language, Shari’ah. AbstrakIntegrasi pengetahuan telah dipelajari sebagai proses menggabungkan informasi baru ke dalam tubuh pengetahuan yang ada dengan pendekatan interdisipliner. Bahasa bukan hanya objek kajian ilmiah linguistik, tetapi juga objek kajian disiplin ilmu lain yang terkait. Pentingnya bahasa dalam banyak studi dan disiplin ilmu telah menyebabkan statusnya sebagai syarat sin qua non untuk pemahaman yang benar tentang objek ilmiah dari disiplin ilmu lainnya. Penguasaan bahasa Arab misalnya merupakan suatu keharusan untuk mempelajari teks-teks agama Islam. Agama Islam menempatkan bahasa pada posisi yang sangat tinggi sehingga secara eksplisit disebutkan dalam al-Qur’an sebagai salah satu tanda keberadaan Tuhan. Kata Kunci: Bahasa, Islam, Linguistik, Syariat.